2021
DOI: 10.21203/rs.3.rs-122176/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expansion of a National Differentiated Service Delivery Model Increases Access to Treatment for HIV and Other Chronic Conditions in South Africa

Abstract: Background: South Africa is home to 7.7 million people living with HIV and supports the largest antiretroviral therapy (ART) program worldwide. Despite global investment in HIV service delivery and the parallel threat of non-communicable diseases (NCDs), there are few examples of integrated programs addressing both HIV and NCDs through differentiated service delivery. In 2014, the National Department of Health (NDoH) launched the Central Chronic Medicines Dispensing and Distribution (CCMDD) program to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this review, the reported leadership and governance-related facilitators include a sequence of events for stepwise model implementation [ 57 ] , availability of training, strong supervision and guidance related activities [ 25 , 38 , 45 , 47 ], and remuneration for lay workers involved in supporting community-based ART delivery models [ 45 ]. Political will at all levels of the health system [ 38 ], policies and guidelines development [ 47 ], strong care linkages [ 47 ], clear referral mechanisms between the community and health facility [ 45 ], provision of free care to access HIV-related services [ 45 ] and availability of central chronic medicine dispensing and distribution program [ 26 ] were identified as critical facilitators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, the reported leadership and governance-related facilitators include a sequence of events for stepwise model implementation [ 57 ] , availability of training, strong supervision and guidance related activities [ 25 , 38 , 45 , 47 ], and remuneration for lay workers involved in supporting community-based ART delivery models [ 45 ]. Political will at all levels of the health system [ 38 ], policies and guidelines development [ 47 ], strong care linkages [ 47 ], clear referral mechanisms between the community and health facility [ 45 ], provision of free care to access HIV-related services [ 45 ] and availability of central chronic medicine dispensing and distribution program [ 26 ] were identified as critical facilitators.…”
Section: Resultsmentioning
confidence: 99%
“…Of all included studies, more than one-third (21) of studies were conducted in South Africa only [12,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41],…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%